A review on involvement of lignin in rice defense against pathogens / Siti Noor Asila Zakaria - Zakaria, Siti Noor Asila (Faculty of Plantation and Agrotechnology, 2019)
This paper reviews the involvement of lignin as a component of plant defence in rice (Oryza sativa). Rice is the most widely consumed foods of the world’s human populations. At the same time, this crop was threatened by the major diseases which are brown spots disease and bacterial sheath blight disease. The pathogen attack in rice could cause in reducing of yield production. Lignin, as defence mechanisms in plants will provide solutions towards the problem faced in the low production of rice. Lignin is a plant secondary metabolite that has various unique functions in plants. It is deposited in the secondary thickened cell wall to prevent pathogen invasion into the plants and also provide strength and imperviousness. The monolignol biosynthetic pathway are usually involving about eleven enzymes, which are L-Phenylalanine ammonia-lyase (PAL), Cinnamoyl-CoA reductase (CCR), Cinnamyl alcohol dehydrogenase (CAD),Caffeic acid O-methyltransferase (COMT), Cinnamate-4-hydroxylase (C4H), Hydroxycinnamoyl transferase (HCT), 4-Coumarate 3-hydroxylase (C3H), Ferulate 5-hydroxylase (F5H), caffeoyl shikimate esterase (CSE), Cinnamoyl CoA O-methyltransferase (CCoAMT) and 4-Coumarate:coenzyme A(CoA) ligase (4CL). This pathway is producing of monomer subunits; p-hydroxyphenyl (H), guaicyl (G) and syringyl (S) units.